2021
DOI: 10.1111/vsu.13625
|View full text |Cite
|
Sign up to set email alerts
|

Survival time of juvenile dogs with oral squamous cell carcinoma treated with surgery alone: A Veterinary Society of Surgical Oncology retrospective study

Abstract: To report the signalment, staging, surgical treatment, and survival time of juvenile dogs treated surgically for oral squamous cell carcinoma (OSCC).Study design: Retrospective study. Animals or sample population: Twenty-five dogs, <2 years of age with OSCC treated with surgery.Methods: Cases were solicited from the Veterinary Society of Surgical Oncology. Data retrieved included sex, breed, age, weight, clinical signs, tumor location, preoperative diagnostics and staging, histopathological diagnosis with marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The recurrence of this tumor after surgery is in agreement with Lascelles et al (2000) who reported an average recurrence of 4-9 weeks (Lascelles et al, 2000). The survival time for SCC dogs after surgery alone with no evidence of metastasis has been reported to be an average of 92 to 4234 days (Sharma et al, 2021). In the current case, the dog died after about 33 days, so it is possible that the dog died from SCC metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The recurrence of this tumor after surgery is in agreement with Lascelles et al (2000) who reported an average recurrence of 4-9 weeks (Lascelles et al, 2000). The survival time for SCC dogs after surgery alone with no evidence of metastasis has been reported to be an average of 92 to 4234 days (Sharma et al, 2021). In the current case, the dog died after about 33 days, so it is possible that the dog died from SCC metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported, SCC is commonly found in dogs with an average age of 8.8 years (Willcox et al, 2019). In addition, some previous reports found an average age of 10 years (Lascelles et al, 2000), but the condition can be found from 4 months to 14 years of age (Łojszczyk et al, 2021;Sharma et al, 2021). The effect of gender on cases of SCC is unclear.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cutaneous and subcutaneous origins are the most frequent neoplasms, representing one-third of all diagnosed tumors in dogs [ 2 ]. Conventional therapies to treat canine tumors have certain disadvantages due to their low specificity, surgical limitations for non-accessible tumors [ 3 ], and the low availability of radiotherapy in some countries [ 4 , 5 , 6 , 7 ]. Due to these issues, immunotherapy is becoming one of the main pillars of anti-tumoral treatment research [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent tumors in dogs are cutaneous and subcutaneous, of epithelial origin, and the gold-standard therapies are either not available (radiotherapy) or are highly invasive procedures (surgery) [ 2 , 3 , 6 ]. The overall incidence of tumors determined to be of epithelial origin in dogs has been reported to be from 26 to 43%, in some cases being very aggressive and invasive tumors [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%